Acupoint Transcutaneous Electrical Nerve Stimulation in Hospitalized COPD Patients with Severe Dyspnoea: A Randomized Controlled Trial - Carles Fernández-Jané PhD; Jordi Vilaró PhD; Lluís Costa-Tutusaus PhD (SAGE Publishing, 2023)
Objective To evaluate the effect of acupuncture transcutaneous electrical nerve stimulation (acuTENS) on the reduction of dyspnoea during acute exacerbation of chronic obstructive pulmonary disease (AECOPD). Methods A multicentric randomized control trial with masked patients and evaluators was carried out. During hospitalization, AECOPD patients received 45 min of acuTENS (experimental group) or sham acuTENS (controls) daily on 5 consecutive days. The trial was conducted at the Hospital del Mar, Barcelona, and Hospital Sant Joan de Déu, Manresa (both in Spain). Dyspnoea and peak expiratory flow were measured daily from the first to fifth days. Length of stay, readmissions at 3 months and adverse events were also analysed. Results Finally, 19 patients with moderately to severely exacerbated COPD were included. Although some tendencies in dyspnoea during day 1 and length of hospital stay were found favouring acupuncture, no significant differences were shown between groups. Conclusions The acuTENS intervention was feasible#well tolerated in AECOPD patients and no important side effects were reported.